Iraq Economic Monitor, Fall 2020 : Protecting Vulnerable Iraqis in the Time of a Pandemic, the Case for Urgent Stimulus and Economic Reforms - World Bank (World Bank, Washington, DC, 2020)
Decades of political, economic and security shocks have shaped major structural imbalances in Iraq's economy, reinforcing Iraq's current fragility trap. Iraq remains as one of the most oil dependent countries in the world. Oil accounted for over 96 percent of exports, 92 percent of government budget revenues and 43 percent of gross domestic product (GDP) in 2019. Overdependence on oil has also increased economic volatility and discouraged investment in other sectors. Multiple security shocks including regional conflicts and ISIS attacks have left little room for non-oil sector growth. An unfavorable business environment has undermined private sector's crucial role in job creation. The large size of the public sector and wage bill rigidity has restricted fiscal space required for investments in human capital and infrastructure and restricted response to economic shocks. Poor service delivery and rampant corruption along with soaring unemployment and poverty rates have led to public grievances even before the global pandemic. Iraq's economy continues to face significant macroeconomic challenges following the twin shocks of the COVID-19 pandemic and collapse in global oil markets. Iraq's GDP shrank by 6.8 percent year-on year (y/y) in the first half of 2020 (H1-20) reversing a steady improving economic growth trend over the previous two years. Depressed global energy demand and the OPEC+ production cut led Iraq's oil GDP to contract by 10.4 percent (y/y) in Q2-20. Since then, oil production declined to reach a five-year low of 3.58 mbpd in August 2020. Lower economic activity was most pronounced in the services sector, which contracted by 20.7 percent (y/y) in Q2-20, following the introduction of lockdowns and curfews in March 2020. This sharp contraction led non-oil GDP to decline by 9.2 percent (y/y) in H1-20. As of September 2020, geo-mobility data showed activity in workplace areas to have partially improved to around 20 percent below their pre COVID-19 levels. However, the surge in COVID-19 cases, which exceeded 400,000 confirmed cases and 10,000 deaths in October 2020, highlights the ongoing nature of the health crisis and the necessity to focus on saving lives to avoid longer term irreversible impacts of the crisis. Iraq's economic outlook hinges on the prospects of global oil markets and the capacity of the healthcare sector to cope with the pandemic. Improved outlook for oil markets and increased production, as part of the OPEC agreement, are expected to drive growth in 2021 and 2022 in the absence of strong reforms. If the health situation improves, growth is projected to gradually rebound from 2.0 percent in 2021 and to 7.3 percent in 2022 with non-oil economy growth projected to bounce back to an average of 4 percent in 2021–22. As such, the fiscal and external pressures are expected to remain as the twin balances remain in deficit.